Safety and efficacy of autologous hematopoietic stem cell transplantation for multiple sclerosis in Norway. (December 2020) - Kvistad, Silje Agnethe Stokke; Lehmann, Anne Kristine; Trovik, Linn Hereide; Kristoffersen, Einar Klæbo; Bø, Lars; Myhr, Kjell-Morten; Torkildsen, Øivind
Background: Hematopoietic stem cell treatment (HSCT) is a promising treatment option for multiple sclerosis (MS), but detailed safety and efficacy measures are still scarce. Objective: To evaluate the efficacy and safety of HSCT in MS. Methods: Retrospective single-center observational study of all MS patients that underwent HSCT in Norway during January 2015 to January 2018. The primary outcome was no evidence of disease activity (NEDA-3) status. Results: A total of 30 patients with a median follow-up time of 26 months (range: 11–48) were evaluated. In total, 25 (83%) achieved NEDA-3 status, and none received disease-modifying treatment after HSCT. For 13 (43%) of the patients, there were sustained improvement in Expanded Disability Status Scale (EDSS) score, and 10 (33%) were working full time after the treatment, compared to only 1 (3%) before treatment. There were no serious treatment-related complications and was no mortality. Five patients (17%) were diagnosed with an autoimmune thyroid disease after the procedure, and 10 (43%) of the women had amenorrhea lasting >12 months and symptoms of ovarian failure. Conclusion: HSCT in MS is an effective and relatively safe treatment option, with few serious complications and no mortality in Norway, so far. However, long-term adverse event with amenorrhea is a common problem.